Prototype Aplikasi Berbasis Mobile Pada Sistem Administrasi Tata Tertib Peserta Didik Menggunakan SMS Gateway - Sri Handoko; Budi Raharjo (Jurnal Publikasi Ilmu Komputer dan Multimedia, 2023)
The system used for the administrative management of the code of conduct on SMA Swadaya Surabaya are still semi-manual record-keeping and reporting that is used is still manual and only as Ms. Office only. And the notification of student violations to parents only by post. This has resulted in frequent errors in recording violations of conduct learners that is unsynchronized between the daily record-keeping violations committed students and the monthly reports made by BK. In addition, the creation of reports requires a long time. And also the difficulty of communication between the school with parents about violations of students. Based on the description of the conditions, then the research aims to design the system of the administration of the code of conduct learners using the SMS Gateway. The system is designed with PHP as programming language, and MySQL Database Server. The method development of the system that is used for the design of the system i.e. SDLC (System Development Life Cycle) consisting of planning systems, analysis systems, design systems, and implementation. The results obtained from this research that is the system of administration code of conduct learners using the SMS Gateway with Mobile Web-based that can help the process of recording and be reporting quick and accurate. This system can also be used as an intermediary of communication between the school and parents regarding violations were done by learners in school.